Reflexos da soberania moderna: o estado de exceção nos séculos XX e XXI - Matos, José Carlos Severo de Oliveira (2021)
This work aims to study the main characteristics of the authoritarian thought and its manifestations in the 20th and 21st centuries, based on the state of exception theory developed by the German jurist, Carl Schmitt. The denomination “exception” designates the phenomenon of the suspension of the legal order through a sovereign decision. Our analysis is based on the Schmitt’s concept of sovereignity, with focus in his reception of the transcendental ideas with religious nature, due to his proximity to other names such as Donoso Cortês, Jean Bodin, Joseph De Maistre, among others. In the structure of the Schmittian thought, it will be considered the aspects of anti-liberalism, anti-formalism and anti-Semitism. The state of exception theory claims the monopoly of the politician, which is based on the distinction between the concepts of friend and enemy. Carl Schmitt is a reactionary jurist who joined Nazism in the year 1933 and provided all the theoretical and political foundation for the achievement of the Totalitarianism in the first half of the last century. With the end of the Second War, the Schmittian theory has come to be observed in the contemporary democracies. Giorgio Agamben says that the exception has become the rule in the current governments. In Brazil, the state of exception has become relevant in the 20th and 21st centuries. In the years of the military regime, the legal order was, in fact, suspended for 21 years, representing the most ominous period in our history. In the 21st century, Brazilian jurists like Pedro Serrano have formulated theories to explain how the exception as state authoritarianism, remains as an actual and worrisome topic for those who study the subject